Enhancement of Heat Exchanger Performance by Using Dimpled Tube - Al-Jabery, Falah F. F. (Al-Khwarizmi Engineering Journal, 2019)
The enhancement of heat exchanger performance was investigated using dimpled tubes tested at different Reynolds numbers, in the present work four types of dimpled tubes with a specified configuration manufactured, tested and then compared performance with the smooth tube and other passive techniques performance. Two dimpled arrangements along the tube were investigated, these are inline and staggered at constant pitch ratio X/d=4, the test results showed that Nusselts number (heat transfer) of the staggered array is higher than the inline array by 13%.  The effect of different depths of the dimple (14.5 mm and 18.5 mm) has been also investigated; a tube with large dimple diameter enhanced the Nusselts number by about 25% for the range of Reynolds number between 4000- 20000. The overall enhancement ratio was used to differentiate the passive technique and comparison of different configurations for the technique itself, the result depicted that the 10 mm dimple diameter with a pitch ratio of X/d= 4 gives better performance than the static mixer and twisted tape techniques. The overall enhancement ratio of the 10 mm dimple diameter is varied from (1.21 to 1.65) that means good performance for a range of Reynolds numbers (4000-20000). This indicates that 21- 65 % of heat transfer area can be saved at the same pumping power compared with the smooth tube heat exchanger.